Factors associated with early initiation of breastfeeding in central Saudi Arabia: a hospital-based survey - Ameinah Thamer Alrasheedi (BMC, 2023)
Abstract Background Early initiation of breastfeeding is central to the success of infant feeding. The World Health Organization (WHO) therefore recommends breastfeeding within the first hour of birth and has set a target to increase the rate to 70% globally by 2030. This suggests the necessity of systematic investigations to capture trends in early initiation of breastfeeding to avail health systems of up-to-date information in the interest of appropriate policy making. Hence, this study was designed to investigate the factors associated with early initiation among mothers who delivered babies in public healthcare facilities in the Al-Qassim Region, Saudi Arabia. Methods The research was a hospital-based, cross-sectional study which featured the recruitment of 546 mothers from March 2021 to June 2021 in five public hospitals. A questionnaire was the tool used for data collection and this was administered via face-to-face, structured interviews. Data were analyzed using binary logistic regression including unadjusted (UOR) and adjusted odds ratio (AOR) with a 95% confidence interval (CI). Results The prevalence of early initiation of breastfeeding was 23.1% (120 of 519 respondents). Maternal and paternal socio-demographic variables, household characteristics, parity, age of the previous child, breastfeeding the previous child or otherwise and the sex of the newborn were not associated with the early initiation of breastfeeding. Mode of delivery and antenatal education about breastfeeding were significant factors. Postnatal care practices were also significant: the provision of help in positioning babies for breastfeeding (AOR 3.5; 95% CI 1.62, 7.57), 24-hour rooming-in (AOR 6.26; 95% CI 1.31, 29.8) and encouragement to practice early initiation of breastfeeding (AOR 3.05; 95% CI 1.71, 5.43) were good, better and the best factors associated with early initiation of breastfeeding respectively. Conclusion The prevalence of early initiation of breastfeeding is poor and represents a threat to child survival in the study area. Postnatal care practices are crucial factors strongly predisposing mothers to early initiation of breastfeeding and should therefore be institutionalized in health policy frameworks to promote the same in Saudi Arabia.